A supramolecular polymeric photoinitiator with enhanced dispersion in photo-curing systems. Issue 11 (3rd February 2020) - Li, Tiantian; Su, Zhilong; Xu, Hongjie; Ma, Xiaodong; Yin, Jie; Jiang, Xuesong
Abstract : A simple and general approach to make the commercial photoinitiator water-soluble and polymeric was developed via supramolecular interactions, which is believed to find wide potential applications in the photo-curing technology. Abstract : Making photoinitiators water-borne and polymeric represents the important advances in photo-curing fields. We, here, reported the design and preparation of a supramolecular polymeric photoinitiator by using the amphiphilic hyperbranched poly(ether amine)s (hPEA) as the host polymer, which can encapsulate guest photointiators via supramolecular interactions. Three kinds of amphiphilic hyperbranched poly(ether amine)s (hPEA101, hPEA211 and hPEA101-EO) were selected as the hosts for the supramolecular system and hydrophobic hydrogen abstracting photoinitiators with carboxyl groups (ATX, CTX, MATX and ABP) were used as the corresponding guests. The resulting supramolecular photoinitiators (hPEA@PIs) exhibit enhanced solubility both in an aqueous solution and acrylate monomer. Moreover, hPEAs have very high loading capacity ( C loading ) for the photoinitiator in aqueous solutions. The photopolymerization kinetics by photo-DSC indicated that this supramolecular photoinitiator (hPEA@PI) can initiate the photopolymerization of a water-soluble monomer, namely acrylamide (AM), rapidly and effectively in water. In addition, the host hPEAs in addition can increase the solubility of the photoinitiator in organic solvents, and in particular, significantly enhance the compatibility between the photoinitiator and acrylate monomers. The hPEA@PI can also photoinitiate the polymerization of hexanedioldiacrylate (HDDA) and trimethylolpropanetriacrylate (TMPTA) with high double bond conversion (DBC). This strategy of using a supramolecular photoinitiator provides a facile approach to get an amphiphilic polymeric photoinitiator with good dispersion in water and oil systems, which will be potential in photo-curing fields.